Computed Microtomography (Micro-CT) in the Anatomical Study and Identification of Solenogastres (Mollusca) - Martínez-Sanjuán, Jesús; Kocot, Kevin; García-Álvarez, Óscar; Candás, María; Díaz-Agras, Guillermo (Frontiers in Marine Science, 2022)
Solenogastres are vermiform marine molluscs characterised by an aculiferous mantle, a longitudinal ventral pedal groove and a terminal or subterminal pallial cavity. Their classification is based in part on the type of mantle sclerites, but identification to even the family level generally requires the study of internal anatomical characters. Taxonomically important internal characters include those related to radular structure, the type of ventrolateral glandular organs of the pharynx and the reproductive system, among others. In order to study their internal anatomical organisation, according to the classical reconstruction method, serial histological sections of specimens are made, from which the 2D internal anatomy of the specimen can be reconstructed manually. However, this is a time-consuming technique that results in destruction of the specimen. Computed microtomography or micro-CT is a non-destructive technique based on the measurement of the attenuation of X-rays as they pass through a specimen. Micro-CT is faster than histology for studying internal anatomy and it is non-destructive, meaning that specimens may be used for e.g., DNA extraction or retained as intact vouchers. In this paper, the utility of micro-CT for studying taxonomically important internal anatomical structures was assessed. Results of the 3D anatomical study of the soft parts of four specimens of three species using micro-CT are presented: Proneomenia sluiteri Hubrecht, 1880, Dorymenia menchuescribanae García-Álvarez, Urgorri and Salvini-Plawen, 2000 and Anamenia gorgonophila (Kowalevsky, 1880). Micro-CT enabled detailed study of most taxonomically important anatomical characters, precise measurements of structures, and observation of the relative position of organs from a variety of angles. However, it was not possible to observe the radula and some details of the ventral foregut organs were not accurate. Despite these limitations, results of this study highlight micro-CT as a valuable tool to compliment histology in the study of solenogaster anatomy and in non-destructively identifying animals to the family and even genus-level.